Prevalence of academic resilience of social science students in facing the industry 5.0 era - Indriyana Rachmawati; Widya Multisari; T. Triyono; Irene Maya Simon; Augusto da Costa (Institute of Advanced Engineering and Science, 2021)
Academic resilience is an individual's academic resilience in facing academic pressure. In fact, in the industry 5.0 era resilience is needed by individuals to face various challenges in the future. This study determined the prevalence of academic resilience of Social Science students in facing the industry 5.0 era. This research employed survey design. The sample was 116 students of Social Sciences who were selected using proportional stratified random sampling technique. The data collection used academic resilience questionnaire. It was tested for validity and reliability with a KMO and Bartlett's Test value of 0.741. The data was analyzed descriptively. Students' academic resilience was shown by having competence, self-confidence, character, commitment, interest, and self-control to overcome difficult situations at hand. Commitment is an important aspect for individuals to be tough in academic situations.